1958
DOI: 10.1115/1.4012256
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Transfer Characteristics of the Rotational and Axial Flow Between Concentric Cylinders

Abstract: This paper considers the convective heat-transfer characteristics of the flow in the annular gap between a rotating inner cylinder and a stationary outer cylinder. Heat-transfer measurements are reported for two gap sizes and various combinations of axial and rotational flows. Both smooth and slotted surfaces were used. Measurements for laminar and turbulent-flow conditions followed the trends predicted by theory. An unusual feature of the results for rotational flow without axial flow is the heat-transfer rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

1971
1971
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 0 publications
0
12
1
Order By: Relevance
“…In the present research, the maximum rotational Reynolds number is 4500 (see Table 1), so according to identified five different regions for CT flow by Murai et al (2008), the flow region is turbulent wavy vortex flow (TWTF). On the other hand, in a simple CT flow Taylor vortices appear in the annulus gap when Taylor number reaches to critical Taylor number ( 3 1.7 10 cr Ta ) (Gazley Jr, 1958 ). Since in this work minimum Taylor number is greater than the critical Taylor number, the Taylor vortices undoubtedly appear inflow.…”
Section: Methodsmentioning
confidence: 65%
“…In the present research, the maximum rotational Reynolds number is 4500 (see Table 1), so according to identified five different regions for CT flow by Murai et al (2008), the flow region is turbulent wavy vortex flow (TWTF). On the other hand, in a simple CT flow Taylor vortices appear in the annulus gap when Taylor number reaches to critical Taylor number ( 3 1.7 10 cr Ta ) (Gazley Jr, 1958 ). Since in this work minimum Taylor number is greater than the critical Taylor number, the Taylor vortices undoubtedly appear inflow.…”
Section: Methodsmentioning
confidence: 65%
“…The thermal conduction in the air gap is carried out in a centrifugal force field, and the air convection in a cylindrical surface has been studied in related references. 31–37 The coefficient in the gap is calculated byhere δ is the air-gap length; Nu represents Nusselt number, which can be calculated by 33 where r1 is the rotor radius (m); β represents empirical coefficient considering surface roughness; and Re is Reynolds number of the airflow in the air gap, which is indicated asAnd in Eq. 37, Recr represents the critical value of Reynolds number, which is written as 38 …”
Section: Heat Transmission Mechanism In the Motorized Spindlementioning
confidence: 99%
“…However, the results from the literature give some uncertainty for what the critical T a m is. For Hwang [26], Hayase [25] and Gazley [16] the instability onset seems to take place for T a m < T a c . Whereas according to the data from Bouafia [21], [23], the vortices appear for higher values of modified Taylor number, and in particular the critical T a m = 3, 900 is measured.…”
Section: Literature Reviewmentioning
confidence: 99%
“…• Laminar flow • Laminar flow plus Taylor vortices • Turbulent flow plus Taylor vortices • Turbulent flow The presence of salient poles on the rotor side considerably changes the boundary conditions of the problem since the air flow is no longer driven by a continuous surface, and recirculations develop in the slots. This affects the critical value for the onset of instability and the rate of convective heat transfer between the rotor and stator surface, which may increase by up to 50% [16]. Thus, the classical correlations from the literature (e.g.…”
Section: Introductionmentioning
confidence: 99%